PARs (and ASPA's) contribution to public administration internationally - Podger, Andrew (2018)
The study and practice of public administration vary in each and every country, yet there are many lessons to be learned internationally. Public Administration Review (PAR) and the American Society for Public Administration (ASPA) have contributed substantially to these lessons over the last 80 years, including for public administration in Australia. That contribution has been particularly in organizational theory and behavioral influence, policy studies, and teaching and research. Australia has tended to emphasize institutions and descriptions of practice. These differences help explain the more limited involvement of practitioners in ASPA and the Institute of Public Administration Australia's too little involvement of scholars. ASPA and PAR have played a leading role in recent years in expanding opportunities for international learning. Such learning requires an appreciation of differences in contexts, including of America's own unique context. Better understanding of Australia's context might lead to a more positive appreciation in the United States of Australia's reform experience. The balancing of scholarly and practitioner perspectives is also required. - Reproduced.
Keywords: Public administration